2020
DOI: 10.1021/acsami.0c13457
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cell-Mediated Self-Assembled Colloidal Scaffolds

Abstract: A critical step in tissue engineering is the design and synthesis of 3D biocompatible matrices (scaffolds) to support and guide the proliferation of cells and tissue growth. The most existing techniques rely on the processing of scaffolds under controlled conditions and then implanting them in vivo, with questions related to biocompatibility and implantation that are still challenging. As an alternative, it was proposed to assemble the scaffolds in loco through the self-organization of colloidal particles medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…For active rods moving in the presence of fixed surface obstacles, an optimal density of obstacles was predicted, which enhances the rods diffusivity for large enough aspect ratio [67], and when active Brownian particles experience a short-range aligning interaction, they form a network of tunnels in the presence of passive particles [68]. Finally, for cellular systems, it is known that the surrounding conditions affect cell motility [69][70][71] where both one-dimensional confinement [72] or two-dimensional substrates can increase cell motility [73].…”
Section: Discussionmentioning
confidence: 99%
“…For active rods moving in the presence of fixed surface obstacles, an optimal density of obstacles was predicted, which enhances the rods diffusivity for large enough aspect ratio [67], and when active Brownian particles experience a short-range aligning interaction, they form a network of tunnels in the presence of passive particles [68]. Finally, for cellular systems, it is known that the surrounding conditions affect cell motility [69][70][71] where both one-dimensional confinement [72] or two-dimensional substrates can increase cell motility [73].…”
Section: Discussionmentioning
confidence: 99%
“…100,[132][133][134][135] Another polymer that has increasingly been used is chitosan, a positively charged polysaccharide obtained through the alkaline hydrolysis of chitin, which can be readily obtained from the exoskeletons of invertebrates such as crustaceans and insects, as well as the cell walls of fungi. 136,137 Polystyrene (PS) is the most commonly used synthetic polymer in commercially available microcarriers for large-scale cell culture, 111,138 however, polymers such as poly(L-lactic acid) (PLLA), poly(glycolic acid) (PGA), PLGA and poly(ε-caprolactone) (PCL) 119,139 have been increasingly used due to their biodegradable properties. Both PLLA 35,98,99,140,141 and PCL 101,142,143 microparticles have previously been co-encapsulated with cells within microcapsules.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Under biological conditions, cells move confined by other cells and by the extra cellular matrix [5,6]. It is reported that cell motility correlates strongly with the surrounding conditions [7][8][9]. For instance, it is known that a one-dimensional confinement can trigger collective migration [10] and that changes in the density of cells in a two-dimensional substrate can lead to an increase in their motility [11].…”
Section: Introductionmentioning
confidence: 99%